1999
DOI: 10.1007/s002650050598
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mating and facultative polygyny in the Panamanian leafcutter ant Acromyrmex echinatior

Abstract: Queen mating frequency of the facultatively polygynous ant Acromyrmex echinatior was investigated by analysing genetic variation at an (AG) n repeat microsatellite locus in workers and sexuals of 20 colonies from a single Panamanian population. Thirteen colonies were found to be monogynous, 5 colonies contained multiple queens, whereas the queen number of 2 colonies remained unresolved. Microsatellite genotypes indicated that 12 out of 13 queens were inseminated by multiple males (polyandry). The mean queen ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…Previous studies with microsatellite DNA markers have shown that lower attines have singly mated queens (Villesen et al 1999;Murakami et al 2000), whereas the most derived higher attines, the Atta and Acromyrmex leafcutting ants, are invariably multiply mated Bekkevold et al 1999;Boomsma et al 1999;Fjerdingstad & Boomsma 2000). Because queen mating frequencies of leafcutter ants are the highest so far documented for ants, these comparative data imply that fundamental changes in selection on the mating system have taken place during the evolutionary history of the attine ants.…”
Section: Introductionmentioning
confidence: 73%
“…Previous studies with microsatellite DNA markers have shown that lower attines have singly mated queens (Villesen et al 1999;Murakami et al 2000), whereas the most derived higher attines, the Atta and Acromyrmex leafcutting ants, are invariably multiply mated Bekkevold et al 1999;Boomsma et al 1999;Fjerdingstad & Boomsma 2000). Because queen mating frequencies of leafcutter ants are the highest so far documented for ants, these comparative data imply that fundamental changes in selection on the mating system have taken place during the evolutionary history of the attine ants.…”
Section: Introductionmentioning
confidence: 73%
“…1) or to false discoveries resulting from multiple tests [supporting information (SI) Table 1]. It was also not due to temporal changes in sperm use because this does not seem to occur in mature colonies of A. echinatior (21) and because the workers and queens were in any case from the same age cohort. There is therefore a significant genetic inf luence on queen-worker caste determination in A. echinatior.…”
Section: Resultsmentioning
confidence: 99%
“…Only the evolutionarily most derived genera of the higher attine ants, the Atta and Acromyrmex leaf-cutting ants, have high queen-mating frequencies (Fjerdingstad et al 1998;Bekkevold et al 1999;Boomsma et al 1999;Fjerdingstad and Boomsma 2000). Recent evidence indicates that the transition from single to multiple queen-mating has occurred only once in the common ancestor of these two genera (Villesen et al 1999(Villesen et al , 2002b.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a similar analysis for the attine fungus-growing ants, another tribe of social insects for which the phylogeny is known (Schultz and Meier 1995;Wetterer et al 1998) and where multiple queen-mating is restricted to the most derived terminal genera, the Acromyrmex and Atta leafcutter ants (Villesen et al 1999(Villesen et al , 2002b. All species of leafcutter ants so far investigated have effective queenmating frequencies of two or above (Fjerdingstad et al 1998;Bekkevold et al 1999;Boomsma et al 1999;Fjerdingstad and Boomsma 2000), so that worker reproduction is not expected to occur in queenright colonies (Ratnieks 1988). However, representatives of the lower attines (Villesen et al 1999;Murakami et al 2000) and the basal genera of the higher attines, Trachymyrmex and Sericomyrmex (Villesen et al 2002b), are exclusively or predominantly singly mated, so that the conflict over male production may be expressed and may at least be partly won by the workers.…”
Section: Introductionmentioning
confidence: 99%